LA EVALUACIÓN ORIENTADA AL APRENDIZAJE DEL INGLÉS - María del Mar Palenzuela Pérez; Noemí Reina Ruz (European Scientific Journal, ESJ, 2014)
Evaluation is important for teachers and students in order to get information about the learning process and, therefore, it will have consequences for the development of the class to determine teaching effectiveness and quality. Students tend to adopt learning methods influenced by the nature of the assessment tasks that sometimes hinder learning methods far from those adequate to the student profile. This paper presents a learner-centered evaluation taking into account the profile of the students and the subject to be evaluated. The study was conducted in a classroom of EFL and has focused on the student’s oral communication skills.